Enhancing the sustainability of cherry blossom landscapes-a case study in Fujian Province, China - Peng, Hongjun; Li, Ping; Zhu, Rong (Frontiers in Forests and Global Change, 2024)
Utilizing flowering cherries to enhance suburban landscapes and attract public recreation holds significant economic and social value. However, the current quality of the cherry landscape is compromised due to the absence of variety selection and planning in planting and design. Based on the analysis of public preference, there is significant importance in boosting the sustainability of cherry blossom landscape. However, related research in this domain still needs to be explored. This study examined four representative cherry blossom landscapes in Fujian Province to assess the landscape quality and growth of existing cherry varieties. Subsequently, an improvement model of cherry blossom landscape quality was developed based on image semantic segmentation, aiming to quantify landscape elements. The findings indicated that: (1) There were a total of 46 cherry varieties blooming from January to March in the four representative cherry blossom landscapes. The health grades distribution was as follow: Grade I accounted for 41.3 %, Grade II for 39.1 %, Grade III for 8.7 %, Grade IV for 6.5 %, and Grade V for 4.4 %. (2) The highest marginal benefit for flake planting was observed when the flowering ratio exceeded 60 % or was less than 15 %. In contrast, the optimal flowering ratio for the linear cherry blossom landscape for maximum marginal benefit was over 30.0 %. (3) The outcomes of the scenic beauty model revealed that the five major factors influencing the scenic beauty were the scene cleanliness (38.04 %), plant color composition (25.59 %), road (17.79 %), plant type (12.88 %) and building (2.70 %). The results of this study provide valuable objective data references for the planning, design and management of cherry blossom landscapes.